Effectiveness of Federal Regulation of Mobile Medical Applications - Sarah Jean Kilker (Washington University Law Review, 2016)
Due to rapid growth and advancement of technology, uncertainty has emerged as to whether some of the medical apps on the market should be considered medical devices, which are subject to stringent regulation by the FDA.The FDA issued final guidelines regarding the regulation of medical apps in September of 2013 and updated the guidance in February 2015, but it has not issued formal regulations. Part I of this Note examines the development of mobile medical health applications and regulation in countries with comparable mobile-app use, and then explores the evolution of the FDA’s position regarding the regulation of such apps. Part II analyzes and critiques current and conceivable regulatory strategies by the federal government, as well as private regulatory organizations such as the United States Pharmacopeial Convention and the Health on the Net Foundation. Part III argues that current FDA regulations are insufficient and suggests a peer reviewer or other organization may be better suited to assess the usability of apps and offer usage guidelines for consumers. Part III also discusses three proposed models for regulation of mobile medical apps. This Note argues that a regulatory approach that includes a peer review system and a non-profit organization that specializes in mobile medical technology will be more efficient and useful to monitor mobile medical apps than the current FDA guidelines.
Keywords: FDA; mobile medicine; apps; regulation